A SUSTENTABILIDADE COMO ESTRATÉGIA DE DESENVOLVIMENTO PARA ÂMBITOS ESPACIAIS PERIFÉRICOS - Vanoni, Elisa A. H.; Ecker, Cleder M. O.; Mauss, Adriano; Dallabrida, Valdir R. (Salão do Conhecimento, 2013)
Resumo